Use of Bacillus pumilus CBMAI 0008 and Paenibacillus sp. CBMAI 868 for colour removal from paper mill effluent - de Oliveira, Patrícia Lopes (Sociedade Brasileira de Microbiologia, 2009)
Bacillus pumilus and Paenibacillus sp. were applied on the paper mill effluent to investigate the colour remotion. Inocula were individually applied in effluent at pH 7.0, 9.0 and 11.0. The real colour and COD remotion after 48h at pH 9.0 were, respectively, 41.87% and 22.08% for B. pumilus treatment and 42.30% and 22.89% for Paenibacillus sp. Gel permeation chromatography was used to verify the molar masses of compounds in the non-treated and treated effluent, showing a decrease in the compounds responsible for the paper mill effluent colour.